Anabolic steroid use and ischaemic stroke in a young fitness enthusiast. Issue 2 (4th February 2021) - Choulerton, James; Guha, Nishan; Squires, Rebecca
Abstract : We report a case of ischaemic stroke in a 34-year-old male recreational bodybuilder following a 3-month period of anabolic androgenic steroid (AAS) use and 1-month period of 'post-cycle therapy' (tamoxifen and clomiphene citrate), the latter treatments aimed at restoring normal endogenous testosterone production after initial AAS use. We hypothesise a transient drug-related prothrombotic state with paradoxical embolisation via an atrial septal defect which was later found on bubble echocardiogram. We highlight a rare but important cause of stroke in younger patients which is relevant given the increasing use of AAS misuse among casual fitness enthusiasts. We explore the various possible mechanisms by which AAS use can increase ischaemic stroke risk in such patients.